HUBUNGAN PENGETAHUAN, POLA MAKAN DAN KEBIASAAN KONSUMSI SAYUR DAN BUAH DENGAN STATUS GIZI PADA REMAJA USIA 15-18 TAHUN DI KELURAHAN DUREN MEKAR, DEPOK - Livia Salsabila (2020)
The nutritional problem of teenagers in Indonesia nowadays are double burden malnutrition. Double burden malnutrition in teenagers occurs because of diet and incorrect nutritional behavior. Diet and eating habits in adolescents who consume foods that are fatty, oily, high of sugar and low intake of fiber related to the lack of consumption of vegetables and fruit. Consumption of vegetables and fruit are less influenced by the level of adolescent knowledge. This research aims to know the relationship of knowledge, diet and consumption habits of vegetables and fruits with nutritional status in adolescents aged 15-18 years in the village of Duren Mekar. This research is an analytical observational research with cross-sectional design. The subject of this study is adolescents aged 15-18 years old who meet the criteria as many as 50 respondents selected by the purposive sampling method. Research Data is obtained by measuring weight, height, filling the nutritional knowledge questionnaire and also using Semi Quantitative-Food Frequency Questionnaire to see the diet and consumption habits of vegetables and fruits. Data analysis using Chi Square test. The results of the study stated that there is no significant link between knowledge (p = 0.699), diet (p = 0.297), vegetable consumption (p = 0.297) and fruit consumption (p = 1.000) with nutritional status in teenagers aged 15-18 years in the village of Duren Mekar.